Ethnobotanical Evaluation in the Province of Pacasmayo, la Libertad, Peru; [Evaluación Etnobotánica en la Provincia de Pacasmayo, Departamento la Libertad, Perú] - Martinez-Salinas, J (MS-Editions, 2025)
The study aimed to determine the importance of ethnobotany in the province of Pacasmayo, La Libertad, Peru, in 2022. Semi-structured interviews were conducted with 95 villagers over 20 years of age, collecting information on 73 useful plant species, distributed in 66 genera and 34 families, with Asteraceae, Fabaceae, Poaceae and Solanaceae being the most representative. Of the total, 67.3% of the species are used for human consumption, 24.6% for medicinal purposes, 1.7% for ornamental uses, 1.2% as animal feed, 2.2% as fuel, 0.75% in construction, 1.9% as bait for wild animals and 0.37% in rituals. Through the Cultural Index (CI), a broad knowledge about plants and their importance in various categories of use was evidenced. The results highlight the relevance of ethnobotanical knowledge for the sustainable use and maintenance of cultural and biological diversity in the region. © 2025, MS-Editions. All rights reserved.